2020
DOI: 10.14245/ns.1938282.141
|View full text |Cite
|
Sign up to set email alerts
|

A New Shielding Curtain for Protection of Intraoperative Radiation During Minimally Invasive Spine Surgery

Abstract: Objective: Gradually increasing number of minimally invasive spine surgery (MISS), there is an increasing risk of radiation exposure to medical personnel during the surgery. We measured the radiation exposure of the operating room personnel during MISS, tried to find the riskiest person, and checked the effectiveness of a new lead-composite shielding curtain. Methods: Radiation exposure of medical staffs (operator, first assistant, anesthesiologist, and scrub nurse) involved in MISS procedures of 35 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The use of Curtain showed the best RPE at the gonad level (90.34%) but the lowest RPE at the eye and thyroid levels (3.38% and 3.12%, respectively). These findings suggest that Curtain is specialized only in gonad protection, which is in accordance with the findings of previous studies (16)(17)(18). Because physicians are exposed to radiation throughout their bodies during interventional procedures, an average RPE of Curtain of 32.28% is not efficient compared with that of other single-protection methods.…”
Section: Discussionsupporting
confidence: 90%
“…The use of Curtain showed the best RPE at the gonad level (90.34%) but the lowest RPE at the eye and thyroid levels (3.38% and 3.12%, respectively). These findings suggest that Curtain is specialized only in gonad protection, which is in accordance with the findings of previous studies (16)(17)(18). Because physicians are exposed to radiation throughout their bodies during interventional procedures, an average RPE of Curtain of 32.28% is not efficient compared with that of other single-protection methods.…”
Section: Discussionsupporting
confidence: 90%
“…There are published reports of radiation shielding in angiography and orthopedic surgery. [19][20][21][22] In our previous study, Inoue et al previously reported the benefit of lead curtains during URS. 7 They hand-made an operative table curtain made from lead and used it to protect against scattered radiation exposure.…”
Section: Discussionmentioning
confidence: 78%
“…Studies to reduce radiation exposure to health care workers have been previously reported. There are published reports of radiation shielding in angiography and orthopedic surgery 19–22 . In our previous study, Inoue et al .…”
Section: Discussionmentioning
confidence: 87%
“…The protection of operators from radiation exposure and avoidance of iatrogenic radiationinduced injuries are high priorities in the introduction of new operative techniques. 14 Various recommendations for different combinations of radiation-shielding devices have been proposed. 15 However, these shielding devices are usually very heavy, and strenuous for surgeons to wear for long periods.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation dose of the operator was highest in C‐arm‐guided minimally invasive spine surgery. The protection of operators from radiation exposure and avoidance of iatrogenic radiation‐induced injuries are high priorities in the introduction of new operative techniques 14 . Various recommendations for different combinations of radiation‐shielding devices have been proposed 15 .…”
Section: Introductionmentioning
confidence: 99%